Hubungan Harga dengan Keputusan Pembelian Aki pada Toko Rn Accu di Punggur, Lampung Tengah - Iryantoro, Lambet (Jurnal Manajemen DIVERSIFIKASI, 2021)
Based on the results of the pre-survey, what became a phenomenon in this study was that there was an imbalance between the sale of batteries at high prices and batteries at medium and low prices. In connection with these problems, the formulation of the problem in this study is "How is the relationship between price and battery purchase decisions?". From these problems, the purpose of this study is to determine the relationship between price and battery purchase decisions. The method used in this research is the explenatory survey method, which is a survey used to explain the causal relationship between two variables through hypothesis testing which is formulated or often referred to as explanatory research. The data analysis techniques used in this study were product moment, partial t test, and r2 determination. Based on data analysis carried out using the product moment formula, it is obtained that the R count of 0.950 is greater than the R table at the 0.05 significance level which indicates that the price is closely related to the purchase decision. The t test shows that the value of T is greater than the T table which explains that the price variable is positively and significantly related to the purchase decision. Furthermore, it is proven by the calculation of R determination which shows the R2 value of 90.3%, which means that the price variable contacts the purchase decision of 90.3. % so that the remaining 9.7% is related to other variables not examined.